PART B: 5th American Caribou Workshop, 19-21 March 1991, Yellowknife, Northwest Territories, Canada. - Skjenneberg (ed. in chief), Sven (Rangifer, 1991)
The 5th American Caribou Workshop was arranged at Yellowkife 1991 with 67 participants. The workshop addressed the issue of how ecological theory can be applied to practical caribou management problems. In addition to that theme, we also chose to highlight cooperative caribou management boards and the conservation and management of woodland caribou. The proceedings was publihed in two parts, part A and part B.
Keywords: proceedings; ACW; Yellowknife; 1991; caribou